Disfunción familiar y rendimiento académico de los estudiantes del noveno año de educación básica del Colegio Nacional Remigio Geo Gómez Guerrero de la ciudad de Huaquillas, período 2012-2013. - Salazar Vega, Danny Omar (2013)
The methods used in this process are, analytic-synthetic historical-comparative case study and troubleshooting, so research is quantitative-mixed, suitable for implementation instruments applied. change strategies that will provide a solution to the problem, action that will affect society and mainly college students are described.